2017
DOI: 10.1186/s12989-017-0191-7
|View full text |Cite
|
Sign up to set email alerts
|

In vivo quantification of quantum dot systemic transport in C57BL/6 hairless mice following skin application post-ultraviolet radiation

Abstract: BackgroundPrevious work has demonstrated size, surface charge and skin barrier dependent penetration of nanoparticles into the viable layers of mouse skin. The goal of this work was to characterize the tissue distribution and mechanism of transport of nanoparticles beyond skin, with and without Ultraviolet Radiation (UVR) induced skin barrier disruption. Atomic absorption spectroscopy (AAS), flow cytometry and confocal microscopy were used to examine the effect of UVR dose (180 and 360 mJ/cm2 UVB) on the skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…This observation is relevant to skin sensitization since the concentration of LC present in the skin has been correlated with increased susceptibility to ACD development. Other in vivo studies confirmed metal nanomaterials including QD are taken up by LC and subsequently transported to lymph nodes (Jatana et al 2017b). In vitro , associations with LC have been shown to be influ-enced by SiNP size and surface functionalization (Vogt et al 2006; Rancan et al 2012).…”
Section: Metal Nanomaterials and Dermal Hypersensitivitymentioning
confidence: 88%
“…This observation is relevant to skin sensitization since the concentration of LC present in the skin has been correlated with increased susceptibility to ACD development. Other in vivo studies confirmed metal nanomaterials including QD are taken up by LC and subsequently transported to lymph nodes (Jatana et al 2017b). In vitro , associations with LC have been shown to be influ-enced by SiNP size and surface functionalization (Vogt et al 2006; Rancan et al 2012).…”
Section: Metal Nanomaterials and Dermal Hypersensitivitymentioning
confidence: 88%
“…Chemical modifications of nanoparticle surface allow for more biocompatible as well as less immunogenic solutions [ 25 ]. Quantum dots (QDs), for instance, one of the most commonly utilized classes of nanoparticles, have a diversity of chemical and optical properties due to the possibility of altering their surface chemistry and size [ 26 ]. In previous studies, CdTe/ZnS QDs [ 15 ], CdSe/ZnS QDs [ 27 ], and CdTe QDs [ 28 ] were used as ILNs detecting minor temperature changes.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical modifications of nanoparticle surface allow for more biocompatible as well as less immunogenic solutions [25]. Quantum dots (QDs), for instance, one of the most commonly utilized classes of nanoparticles, have a diversity of chemical and optical properties due to the possibility of altering their surface chemistry and size [26]. In previous studies, CdTe/ZnS QDs [15], CdSe/ZnS QDs [27], and CdTe QDs [28] were used as ILNs detecting minor temperature changes.…”
Section: Introductionmentioning
confidence: 99%